Thermophilic Archaeal Diversity and Methanogenesis from El Tatio Geyser Field, Chile. Issue 3 (16th March 2017) - Plenge, Megan F.; Engel, Annette S.; Omelon, Christopher R.; Bennett, Philip C.
ABSTRACT: The hydrothermal fluid chemistry at El Tatio Geyser Field (ETGF) in northern Chile suggests that biogenic CO2 –CH4 cycling may play an important role in water chemistry, and relatively low sulfate (0.6–1 mM) and high molecular hydrogen (H2 ) concentrations (67–363 nM) suggest that methanogenic Archaea are present in ETGF microbial mats. In this study, δ 13 C analysis of dissolved inorganic carbon and methane was not indicative of biogenic methane production (δ 13 CCH4 values ranging from −15‰ to −5.3‰); however, methanogenic Archaea were successfully cultured from each of the hydrothermal sites sampled. Sanger sequencing using universal Archaea primers identified putative methanogenic orders with varying metabolic capabilities, including Methanobacteriales, Methanomicrobiales and Methanosarcinales.